The Beneficial Effects of Physical Activity on Impaired Adult Neurogenesis and Cognitive Performance - Lafenetre, Pauline; Leske, Oliver; Wahle, Petra; Heumann, Rolf (Frontiers in Neuroscience, 2011)
Neurogenesis occurs in two neurogenic zones in the adult brain: new neurons are born at the subventricular zone of the lateral ventricles and then migrate to the olfactory bulb, and at the subgranular zone to integrate the granular cell layer of the dentate gyrus. The hippocampus is involved in learning and memory, and the generation of new hippocampal neurons has been suggested to be a new form of plasticity implicated in these processes. In the last decades, diverse intrinsic and epigenetic factors have been identified to influence adult neurogenesis but the underlying mechanisms remain unclear. In a recent study, Lafenetre et al. (2010) showed the beneficial influence of physical voluntary activity via Brain-Derived Neurotrophic Factor on adult neurogenesis and cognitive performance in a transgenic mouse, the synRas mouse. Here we review how hippocampal neurogenesis can be regulated by environmental factors and the possible role of the newly generated cells in learning and memory.